Construction and validation of the instruments to compare teachers’ conceptions and school textbooks of 19 countries: the European Biohead-Citizen project - Carvalho, Graça Simões de (2007)
The FP6 European project Biohea-Citizen involves 19 countries and intends to compare syllabuses and textbooks as well as pre-service and in-service teachers’ conceptions (systems of values as well as scientific knowledge). In this work we describe the collective construction process of the grids for textbook analysis, their validation and application in textbooks and we give exemplificative results obtained by the project consortium. Similarly, we present the methodology used for the questionnaire construction, including its translation into all countries languages and the methods for the translation validation as well as the pilot test used for analysing questions reliability and identifying the discriminating ones by using a MCA (Multiple Components Analysis), in order to produce the final questionnaire to be applied in all countries of the Biohead-Citizen project.